An Unusual Cause of Hypoxia: Ventricular Septal Defect, Pulmonary Artery Atresia, and Major Aortopulmonary Collaterals Diagnosed in the Adult Cardiac Catheterization Lab. (27th January 2020) - Bravo-Jaimes, Katia; Walton, Brian; Tung, Poyee; Smalling, Richard W.
Abstract : The association of pulmonary atresia, ventricular septal defect (VSD) and major aortopulmonary collaterals (MAPCA) is an extreme form of tetralogy of Fallot (TOF). It carries a high mortality risk if not intervened on during infancy with only 20% of unoperated patients surviving into adulthood. We present the case of a 40-year-old man who presented for evaluation prior to retinal surgery and was found to have hypoxia and a loud murmur. Cardiac catheterization was performed in the general catheterization laboratory, demonstrating a membranous VSD, pulmonary atresia, and MAPCA. We highlight the challenges and limitations that an adult interventional cardiologist may have when encountering these patients.